2002
DOI: 10.1093/jac/dkf130
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of cefepime in patients with Gram-negative infections

Abstract: We conducted a prospective, open-label study to delineate a relationship between exposure and outcomes in 36 patients treated with cefepime. Twenty patients had documented Gram-negative infections. Timed blood and urine samples were obtained at steady state to determine pharmacokinetic and pharmacodynamic parameters. Microbiological success was significantly correlated with the proportion of the dosing interval that cefepime concentrations exceeded 4.3 x MIC. Our results support in vitro data that suggest bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
183
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(192 citation statements)
references
References 8 publications
7
183
0
2
Order By: Relevance
“…The emergence of resistance during drug exposure could be due the amplification of a resistant mutant(s) present at the baseline. The drug exposure necessary to suppress resistance emergence (C min /MIC ϭ 6) appeared to be consistent with those from previous studies, which suggested that the bactericidal activities of ␤-lactams were maximized at 4ϫ to 6ϫ the MIC (4,16,29), but greater than the widely accepted optimal pharmacodynamic threshold(s) for the ␤-lactams (T Ͼ MIC ϭ 40 to 50%). It is important to recognize that our study design is different from those of most pharmacodynamic studies.…”
Section: Discussionsupporting
confidence: 86%
“…The emergence of resistance during drug exposure could be due the amplification of a resistant mutant(s) present at the baseline. The drug exposure necessary to suppress resistance emergence (C min /MIC ϭ 6) appeared to be consistent with those from previous studies, which suggested that the bactericidal activities of ␤-lactams were maximized at 4ϫ to 6ϫ the MIC (4,16,29), but greater than the widely accepted optimal pharmacodynamic threshold(s) for the ␤-lactams (T Ͼ MIC ϭ 40 to 50%). It is important to recognize that our study design is different from those of most pharmacodynamic studies.…”
Section: Discussionsupporting
confidence: 86%
“…Studies in animal infection models have shown that, for most ␤-lactams, concentrations do not need to exceed the MIC for 100% of the dosing interval to achieve significant antibacterial effects (8,9), and bactericidal effects of carbapenems against Escherichia coli and Pseudomonas aeruginosa in a murine thigh infection model are observed when plasma drug concentrations are above the MIC for 40% of the dosing interval (20). Moreover, optimal killing properties have been observed in critically ill patients when concentrations are maintained at 4ϫMIC, with higher concentrations providing little added benefit (21,22). However, there is no consensus regarding which strategy (T ϾMIC versus T Ͼ4ϫ MIC ) is better.…”
Section: Discussionmentioning
confidence: 99%
“…Even the NCCLS frequently relies on healthy-subject data to assess the viability of MIC breakpoints. When possible, PK data should be derived from the population of interest (1,12,22,30,32,33). In summary, 3.375 g of piperacillin-tazobactam given intravenously every 6 h performed well, achieving excellent target attainment rates for MICs of Յ8 (piperacillin) and 4 (tazobactam) mg/liter.…”
Section: Discussionmentioning
confidence: 99%